Effective buffer layer thickness of La-doped CeO2 for high durability and performance on La0.9Sr0.1Ga0.8Mg0.2O3-δ electrolyte supported type solid oxide fuel cells. Issue 4 (April 2021) - Hwang, Kuk-Jin; Jang, Mi; Kim, Min Kyu; Lee, Seok Hee; Shin, Tae Ho
Graphical abstract: Abstract: Solid oxide fuel cells (SOFCs) have been gaining increased attention in the energy sector. Commonly, yttria-stabilized zirconia is widely employed as commercial electrolyte, however, resulted in drawbacks such as high-temperature operating and low conductivity which negatively affect the durability and efficiency. Thus there are many efforts to find high-ionic conductors. From the point of manufacturing, the major difficulty of LaGaO3 -based electrolyte as a high-ionic conductor is its incompatibility with commercial Ni-based anodes during high-temperature processes as well as operating. Several interlayers have been introduced to prevent the reaction between LaGaO3 -based electrolyte and Ni-based anode. In this study, we investigate the optimal thickness of the La-doped CeO2 (LDC) interlayer by the screen-printing method using La0.9 Sr0.1 Ga0.8 Mg0.2 O3- δ for the commercial electrolyte supported SOFCs. As a result, the superior power performance of 2.2 W·cm −2 at 1123 K is achieved through the optimized LDC thickness of 20 μm through not lab-scaled but commercial ceramic manufacturing processing.